2004
DOI: 10.1111/j.1742-4658.2004.04494.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of olfactory receptors in yeast and development of a bioassay for odorant screening

Abstract: The olfactory receptors (ORs) are a large group of proteins belonging to subfamily I of G protein coupled receptors (GPCRs) that bind odorant ligands. These receptors are predicted to contain seven transmembrane helices that change their relative orientation upon odorant stimulation, resulting in the conformational change of the receptor and productive interaction of its intracellular loops with G olf , the a subunit of the heterotrimeric G protein [1][2][3]. Several lines of evidence suggest that the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
99
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 47 publications
(90 reference statements)
5
99
1
Order By: Relevance
“…Some ORs, including human OR1740, were reported not to heterodimerize with a non-olfactory GPCR, the ␤ 2 -adrenergic receptor (15). Our previous studies (6,16,17), in line with others (18,19), showed a bell-shaped OR dose-response curve upon odorant stimulation. Several assumptions have been raised to elucidate the decreased OR response at high ligand concentrations (20 -22).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Some ORs, including human OR1740, were reported not to heterodimerize with a non-olfactory GPCR, the ␤ 2 -adrenergic receptor (15). Our previous studies (6,16,17), in line with others (18,19), showed a bell-shaped OR dose-response curve upon odorant stimulation. Several assumptions have been raised to elucidate the decreased OR response at high ligand concentrations (20 -22).…”
supporting
confidence: 63%
“…For this purpose, we heterologously expressed the human OR1740 receptor under optimized experimental conditions in the yeast Saccharomyces cerevisiae (17,23) and investigated its homo-oligomerization status. Besides a biochemical approach, we used bioluminescence resonance energy transfer (BRET), a well developed biophysical technology employed largely in the past decade to explore GPCR oligomerization to monitor not only OR homodimerization but also the odorant ligand-mediated conformational changes in the receptors.…”
mentioning
confidence: 99%
“…In the framework of this project, an OR and an appropriate G α protein were co-expressed in yeast cells [2] from which membrane nanosomes, with size homogenized to around 50 nm by sample sonication, were prepared.…”
Section: Nanosomes From Sniffing Yeastsmentioning
confidence: 99%
“…Such systems are easily adaptable for a high throughput format (Minic et al, 2005a). Upon stimulation of the olfactory receptor by its odorant ligands in yeasts engineered to co-express either rat I7 or human OR 17-40 receptor and the mammalian Gα subunit, an activation of a MAP kinase signaling pathway takes place, which induces the synthesis of a functional reporter luciferase (Minic et al, 2005b). In that way bioluminescence responses are detected upon odorant binding to the receptor.…”
Section: Bioelectronic Noses Based On Whole Cells Expressing Olfactormentioning
confidence: 99%